Birkhoff center of Almost Distributive Fuzzy Lattice - Berhanu Assaye Alaba; Gerima Tefera Dejen (LPPM Institut Teknologi Sepuluh Nopember, 2017)
The concept of Birkhoff center B_A(R) of an Almost distributive fuzzy lattice (R,A) with maximal element is introduced. We also prove that BA(R) is relatively complemented ADFL and product of ADFL is a gain ADFL.